Physical activity of students in the era of globalization - Starościak, Wojciech; Guła-Kubiszewska, Halina; Kałwa, Małgorzata; Dębska, Urszula (Journal of Education, Health and Sport, 2016)
Purpose. The analysis of physical activity of the contemporary students. Do the students with mostly reported health problems engage in any forms of activity at all? Is the presence of health problems a factor differentiating the level of physical activity of the researched students? Methods. Survey, International Physical Activity Questionnaire IPAQ (short). 1153 male students (n=538) and female students (n=615) were tested: (Wroclaw University School of Physical Education) (n=953) and University of Wroclaw (n=200). Results. The tested men declared higher than women levels of physical activity: (t-Student 4,41; p 0.00). The AWF students declare a significantly higher level of physical activity than the University students (t-Student 7,52; p 0.00; 12,81; p 0.00; 10,79; p 0.00). The subjects involved in training declare a significantly higher level of physical activity (t-Student 7.09; p 0.00; 13,24; p 0.00; 11,22; p 0.00). Among the respondents’ reported pain complaints headaches differentiate the respondents as regards the declared level of physical activity of high and moderate intensity (n=237). Conclusions. Physical education students undertake physical activity on a high and moderate level more often than students of other pedagogical sciences. The main differentiate factors: sex, specialist education profile and sports activity. A larger proportion of the AWF subjects reports problems connected with the lumbar spine pains whereas the university students mainly complain of headaches. The female university students reporting headaches less frequently undertake physical activity on a high and moderate level.